Establishment of male‐specific sequence‐tagged site markers in Asparagus officinalis: An efficient tool for sex identification. (1st April 2022) - Ahmad, Naveed; Tian, Ruizheng; Li, Guanghui; Zhao, Chuanzhi; Fan, Shoujin; Sun, Jie; Zhao, Shuzhen; Wang, Xingjun
Abstract: Garden asparagus is a major dioecious plant that serves as a model for understanding sex determination and sex chromosome evolution. The shared cytogenetic homology of the sex chromosomes, with the exception of a mega base region missing from the X chromosome, has considerably hindered the identification of male and female plants. In this study, two male‐specific sequence‐tagged site (STS) markers Asp‐YS1 and Asp‐YS2, located on the Y chromosome, were discovered for early sex identification. The Asp‐YS1 and Asp‐YS2 markers were particularly effective in amplifying a fragment of 490‐bp and 296‐bp, respectively. Most of the male progenies of selected cultivars, and one homozygous male cultivar ('Y14'), showed male‐specific amplification using these two markers. Of the 24 tested cultivars, the results of 21 cultivars demonstrated male‐specific amplification using the newly identified STS markers suggesting greater applicability and higher specificity over the previously existed Asp1‐T7sp marker, which is limited to some commercial cultivars. These findings presented the establishment of an efficient molecular method for sex identification in asparagus, enabling the rapid selection of male parental lines in future breeding programmes.